2015
DOI: 10.1186/s12957-015-0446-4
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta-analysis of the diagnostic accuracy of pyruvate kinase M2 isoenzymatic assay in diagnosing colorectal cancer

Abstract: BackgroundScreening programmes exist in many countries for colorectal cancer. In recent years, there has been a drive for a non-invasive screening marker of higher sensitivity and specificity. Stool-based pyruvate kinase isoenzyme M2 (M2-PK) is one such biomarker under investigation. The aim of this systematic review and meta-analysis is to determine the diagnostic accuracy, sensitivity and specificity of M2-PK as a screening tool in colorectal cancer.MethodsA literature search of Ovid Medline, EMBASE and Goog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 16 publications
(31 reference statements)
2
20
0
1
Order By: Relevance
“…Some articles reported the diagnostic value of PKM2 in liquid serum for non-small-cell lung cancer 10 and in feces for colorectal cancer. 9 However, the detection of PKM2 in liquid biopsies (serum or feces) was not recommended for use alone as a screening tool for non-small-cell lung cancer and colorectal cancer because of its moderate sensitivity and specificity. Compared to the qualitative evaluation of PKM2 expression in cells or tissues, the measurement of PKM2 in liquid biopsies is quantitative, rapid, simple, and samples can be collected without using invasive techniques, which makes it easier for repeated testing and also makes it convenient for clinical application.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some articles reported the diagnostic value of PKM2 in liquid serum for non-small-cell lung cancer 10 and in feces for colorectal cancer. 9 However, the detection of PKM2 in liquid biopsies (serum or feces) was not recommended for use alone as a screening tool for non-small-cell lung cancer and colorectal cancer because of its moderate sensitivity and specificity. Compared to the qualitative evaluation of PKM2 expression in cells or tissues, the measurement of PKM2 in liquid biopsies is quantitative, rapid, simple, and samples can be collected without using invasive techniques, which makes it easier for repeated testing and also makes it convenient for clinical application.…”
Section: Discussionmentioning
confidence: 99%
“…During tumor formation, PKM2 will gradually replace other tissue-specific isoenzymes until it finally becomes the dominant subtype. 9 The high expression of PKM2 in various tumor tissues, blood, and stool makes it a potential biomarker for tumorigenesis and tumor invasion. 10 Furthermore, several publications have reported the prognostic value of PKM2 in DSN, but the results of these studies are controversial or inconclusive.…”
Section: Introductionmentioning
confidence: 99%
“…The test is based on the detection of proteins in stool derived from neoplastic colonocytes. A recently reported meta-analysis of studies comparing M2-PK with colonoscopy reported a pooled CRC sensitivity and specificity of 79 and 80 %, respectively [ 50 ].…”
Section: Protein Markersmentioning
confidence: 99%
“… 71 A recent meta-analysis of eight studies of M2-PK with a cutoff value of 4 U/mL showed a pooled CRC sensitivity, specificity and accuracy of 79% (confidence interval [CI], 73% to 83%), 80% (CI, 73% to 86%), and 85% (CI, 82% to 88%), suggesting that this marker may have potential as a screening test. 75 However, further studies are needed in a screening population to accurately quantify its test characteristics.…”
Section: Other Noninvasive Markersmentioning
confidence: 99%